Two late pleistocene members of the white-grub complex, one of the most destructive insect pests of turfgrasses - Ramírez, Leonardo César (2016)
We report the record of two members of one of the most destructive insect pests of turfgrasses from the Late Pleistocene of the Pampean region. The presence of Cyclocephala signaticollis and Diloboderus abderus 12,000 years BP enables us to consider them as paleobio-indicators besides studying them as agricultural pests. This work constitutes the very first record of the genus and species, and the first Quaternary record of Dynastinae in South America. Moreover, this is one of the first paleoentomological studies that take in consideration beetles as bioproxies for the Quaternary of Argentina, and allows us to adjust the paleoclimatic inferences made for the region. This finding argues against the classic interpretations that indicate arid environmental conditions in the Pampean region during the first pulses of post-glacial climate recovery.